Engineering mechanics, volume 1 : statics - Meriam, J. L. [ (James L.)]; Kraige, L. G. [ (L. Glenn)] (Wiley, 2013)
The 7th edition of this classic text continues to provide the same high quality material seen in previous editions. The text is extensively rewritten withupdated prose for content clarity, superb new problems in new application areas, outstanding instruction on drawing free body diagrams, and new electronic supplements to assist readers